The effect of dietary intervention and physical activities on the lipid profile of obese children - Fatimah Dewi Atikah; Nurzahara Siddik; Tiangsa Br Sembiring; Ani Ariani (Indonesian Pediatric Society, 2009)
Background Obesity is defined as body weight increase due toexcessive fat accumulation. Obesity during childhood and teenageyears is related to cardiovascular risks including hyperinsulinism,hypercholesterolemia, decreased high density lipoprotein (HOI),and hypertension. The principles of managing obesity are reducingenergy intake and increasing energy use, e.g., by increasing physicalactivities, changing life habits and, most importantly by involvingfamily in the therapeutic process.Objective To evaluate the effect of dietary intervention andphysical activity on obese children.Methods Seventy-six obese primary school children wererandomly allocated to either receive intervention (diet andphysical activities) or no intervention. At the beginning of thestudy, lipid profile was measured in all subjects. Subjects in theintervention group were asked to reduce calorie intake by 200 -500 kCal per day, and participating in a walk of 20-30 minutes forfive days per week over a period of one month. After one month,the lipid profile of both groups was remeasured and compared.Results After one month, 7 3 children had successfully completedthe study and had complete data for analysis. There was asignificant change in the mean HOL level before intervention(47.3 [SO 36.2] mg/dl) compared with after intervention (100.5[SO 35.7] mg/dl, P<0.05) in the group where intervention wasimplemented.Conclusion There are no significant differences in serum lipidvalues after intervention in both groups.